Aspects of current research to combat Fusarium wilt of banana with a special focus on TR4. Brief proceedings of an RTB virtual mini-symposium. FP3 Resilient Crops - Cluster BA3.3 Fungal and Bacterial Wilts. - Johnson, Vincent; Blomme, Guy; Mahuku, George S.; Dita, Miguel (Bioversity International and the International Center for Tropical Agriculture, 2021)
Sharing both recent research results and plans for future studies are vital components of RTB’s strategy to contribute to tackling the threat posed by Foc TR4, and it was for this reason that researchers from BA3.3 convened a mini symposium entitled ‘Aspects of current research to combat Fusarium Wilt of banana with a special focus onTR4’. This brought together more than 60 researchers from across the world for a two-day virtual exchange of cutting-edge research presentations and discussion. Importantly, the results presented are to be published through a special issue of the Journal of Fungi. The work presented in this booklet, which summarizes the proceedings of the mini symposium, constitutes cutting-edge research to address the challenges posed by Foc TR4 that threatens Cavendish as well as other key susceptible cultivars. The research reveals new insights into the spread of Foc TR4 in southern Africa, the Greater Mekong Delta, and Latin America; evaluating biocontrol agents; the survival of Fusarium spores in water; the effects of nematodes and weevils in pathogen spread and infection; and in breeding for resistance. There are great opportunities to harness potential synergies from the many complementarities revealed in the symposium, and a need to scale the research from in vitro to field studies, with the ultimate goal of implementing scalable findings at farm and plantation level. Fusarium wilt will continue to be a challenge for banana producers in the near future. However, as control technologies described here are scaled out, there is real hope that production of what is one of humanity’s most treasured fruits will be restored and that livelihoods of all those that depend on it will be enhanced.